2002
DOI: 10.1001/archotol.128.6.687
|View full text |Cite
|
Sign up to set email alerts
|

Success and Predictability of Provox Prosthesis Voice Rehabilitation

Abstract: Because of its safety and simplicity, tracheoesophageal puncture has become a state of the art method for voice rehabilitation after total laryngectomy. The short-term superiority of voice prosthesis in voice rehabilitation over esophageal speech rehabilitation must be seen in light of comparable long-term success rates of the 2 methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…This is similar to previous reports in the literature depending on the rating scale used, the extent of surgery and the patient-related comorbidities [10][11][12] . The low tone of speech was a consistent source of discontent amongst valve users [4] .…”
Section: Discussionsupporting
confidence: 91%
“…This is similar to previous reports in the literature depending on the rating scale used, the extent of surgery and the patient-related comorbidities [10][11][12] . The low tone of speech was a consistent source of discontent amongst valve users [4] .…”
Section: Discussionsupporting
confidence: 91%
“…Device‐life assessment has received quite a bit of attention over the last two decades of indwelling voice prosthesis research, but ever since the discovery that biofilm formation with its most visible end result, the growth of Candida species,9 it is obvious that silicone rubber voice prostheses remain limited in their functional survival. Worldwide there are considerable differences in device life published, with the shortest ones in Western Europe (median, 3 months; mean, 5–6 months), and the longest in Mediterranean countries and India, with the United States in between (mean, 9–12 months) 6, 10–15. Most likely, these differences are caused by differences in biofilm buildup, which have been hypothesized to have a relation with differences in diet in these areas 16, 17.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies of both TEP procedures have been reported with success rate that ranges from 30 to 93% [4] If we look in the Indian contingent perspective, the first account of this procedure is available from Hazarika et al in 1990 [5], since then many centers have taken this work but only few have reported their experiences [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%